A 21-Year Review of Research on the Effect of Internationalization on Firm Financial Performance and Research Agenda - Anh, Tran Que; Van, Dut Vo (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 1 No 2, 2021)
The objective of this paper is to review the effect of internationalization on firm financial performance and to propose a research agenda in the international business field. By systematically searching the relevant database, twenty-five related studies published in journals indexed in the Web of Science - Clarivate Analytics and Scopus in the period from 1998 to 2019 - were selected and reviewed. The study applied the meta-analysis method to detect the limitations of prior studies. Reviewing results reveal that most of the empirical studies concluded the positive effect of firms’ internationalization on their financial performance; while the nonlinear (U-shaped, or inverted U-shaped or S-shaped) relationship was confirmed by others. Building upon such research gaps, the study proposes research model for such a relationship and the moderating role of state ownership and CEO duality on the association to improve the robustness of future studies in the field by integration.